The Production Evaluation of Lais Fish (Kryptopterus sp.) Culture in Wetlands - Danang Yonarta; Ferdinand Hukama Taqwa; Mohamad Amin; Mirna Fitrani; Muslim; Mochamad Syaifudin (Quagga: Jurnal Pendidikan dan Biologi, 2023)
This study aimed to examine the technical and economic feasibility of lais aquaculture production. A cultivation activity was done in order to increase profits. Primary data was collected by interviewing fish cultivators and secondary data was obtained from related references. The bioecological characteristics of lais fish made this fish a candidate for aquaculture commodities paying attention to the management and technology used. Various technical aspects of production need evaluated continuously, including site selection, seed stocking, feeding, water quality management, fish health, harvesting, and marketing. Referring to the components of the evaluation results which were very lacking. Farmers need partners as mentors and access to several facilities to support production components that have not been maximized, one of which is the provision of best practices of fish handling certified superior lais fish fry.